(untitled) (Research, Society and Development, 2021)
This research aims to observe the influence of aerobic exercise associated with the use of corticosteroids and aqueous extract of the stem bark of Ximenia americana L. in the treatment of Chronic Obstructive Pulmonary Disease. Three doses of papain via the nasal route were used in seven groups of male Wistar rats in order to induce pulmonary inflammatory response. The groups were divided into G1 (exercise + inflammation + steroids), G2 (exercise + inflammation), G3 (inflammation + exercise + X. americana), G4 (inflammation + X. americana), G5 (exercise + inflammation + X. americana + steroids), G6 (inflammation) and G7 (control). After the animals were euthanized, bronchial-alveolar lavage was performed, and the heart and left lung were collected for histomorphological analysis (H.E., P.A.S. and Masson’s trichrome stains). It was found that the treatments performed in groups G1, G2, G3, G4, G5 were successful when compared to G7, with an equivalence of the treated groups in terms of RV wall thickness in relation to G6. Furthermore, through the preparations stained with H.E. from treated animals, dilated air spaces and small infiltration of inflammatory cells are evident. Qualitative analysis of slides stained by P.A.S. shows that there is a smaller number of mucus-producing goblet cells in preparations from rats exposed to a combination of treatment regimens, compared to groups in which there was only one form of treatment. The aqueous extract of X. americana stem bark had a significant contribution in the treatment of COPD, as well as aerobic exercise.